Carbon and water footprints in Brazilian coffee plantations - the spatial and temporal distribution - Martins, L.D. (2018)
The future of many coffee growing regions, such as Brazil, depends on strategies to allow the minimization of the negative impacts of climate change. Still the own contribution of coffee cultivation for global warming is largely unknown. Water and carbon footprints are concepts that indicate the potential negative impact of a specific product, underlining which part of the process is the major responsible for it. In this context, the objective of this study was to quantify and spatialize the water and carbon footprints from coffee crop in different regions of Brazil, and to find the proportional weight of coffee production in the total emission of CO2 and water consumption in the context of Brazilian agriculture. For this end, water and carbon footprints were estimated and spatialized for Brazilian regions along 10 productive seasons (from 2004/2005 to 2014/2015), based on data of plantation area (ha) and coffee production (tons of beans). It is concluded that the estimates of annual carbon and water footprints were 19.791 million t CO2-equivalent and 49,284 million m3 of water, with higher values from the Southeast region. This corresponded to a moderate (ca. 5%) value for the emissions of greenhouse gases, but a relevant water footprint in the context of Brazilian agriculture